KEPUASAN KERJA DITINJAU DARI MOTIVASI KERJA PADA KARYAWAN KONTRAK DI PT.X - RATNA DYAH SURYARATRI; MELIA RIZANATI (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
This purpose of this study is to find how much influence the work motivation on job satisfaction on contract employee at PT.X. Participants in the study are contract employee aged 20-40 years. Thes research use quantitative approach with instrument in the form of questionnaire. Instrument used based on indicators of two variables. Sampling technique in this research using non probability sampling, particulary purposive sampling and saturated sampling is used in the study. Data collected by questionnaires that have been tested for validity and reability. Data analysis using Statistical Product and Service Solution (SPSS) version 23. Based on data analysis results indicate that motivation has a positive relationship to job satisfaction with value of 0,571 with significant 0.000. based on the result value of R_Square = 0,326 or get coefficient value equal to 32,6%, which means that influence of motivation to job satisfaction equel to 32,6%.